OWNERSHIP STRUCTURE AND BOARD STRUCTURE ON FIRM PERFORMANCE : MODERATING EFFECT OF POLITICAL CONNECTIONS - Ivone Ivone; Shellen Shellen (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
The purpose of this study was to examine the relationship between ownership structure and board structure as well as the moderation of political connections in Indonesian stock exchange companies using the dummy method. The object of this research uses the necessary data collection methods. This study uses data on companies listed on the Indonesian stock exchange as the research sample. Companies taken from 2016 to 2020. The research sample used was 1748 data from 437 companies that matched the predetermined research criteria and qualifications. The use of SPSS and Smart PLS software to test the sample data of this study.